Marketing Communication Strategy To Attract Prospective Customer Investment PT IBF Surabaya Branch - Laurita, Maria Vanessa; Tresyanto, Citra Anggraini (Journal Of Islamic Ekonomic and Business, 2022)
This study aims to determine the marketing communication strategy of PT IBF Surabaya Branch in attracting investment interest in prospective customers and the problems in implementing marketing communication strategy. This research was conducted with as qualitative descriptive with data collection techniques using interviews and observation. The result showed that the most superior marketing communication strategy by PT IBF was the marketing mix (7p) combined with the marketing process and can maximize personal selling before compiling messages to be conveyed to customers regarding products, transaction processes using the Meta Trader 4 application and basic methods. Advertising methods are in accordance with the current situation which use social media a lot with company information and testimonials become easier to attract the attetion of customers